Kemampuan Berpikir Tingkat Tinggi, Peserta OSK Matematika Tingkat SD, dan Strategi Think, Talk, And Write - Makur, Alberta Parinters; Prahmana, Rully Charitas Indra; Gunur, Bedilius (Mathematics Education Journal, 2018)
This research begins with the formation of preparatory classes towards OSN Mathematics at Manggarai-NTT Regency level. This is based on the evaluation of the implementation of the Math Olympiad at the elementary level held by the Mathematics Education Department STKIP Santu Paulus. This study aims to improve students’ higher order thinking skills by using Think, Talk, and Write (TTW) strategy in introductory olympiad class. It was action research conducted at Manggarai District with six students taken from different schools selected based on their mathematics achievement. Data were obtained through observation and test. The data analysis and interpretation show that the implementation of Think, Talk, and Write (TTW) strategy can improve students' higher order thinking skills. This can be seen from the increase in the average value of test results in each cycle that is Pre cycle 51.3; cycle I 62.2; and cycle II 71 followed by improvement of learning mastery with presentation of value of each cycle that is pre-cycle 0%; cycle I 50%; and cycle II 83,3%. In particular, one of the students became the first winner in OSK Matematika at Manggarai District level.